2016
DOI: 10.3892/or.2016.5104
|View full text |Cite
|
Sign up to set email alerts
|

Expression of DNA methyltransferases and target microRNAs in human tissue samples related to sporadic colorectal cancer

Abstract: Abstract. Tissue microenvironment functions as a pivotal mediator in colorectal carcinogenesis, and its alteration can cause some important cellular responses including epigenetic events. The present study examined histologically altered tissue structure, DNA methyltransferases (DNMTs) and their corresponding expression of target microRNAs (miRNA). Tissues resected by surgery were from primary colorectal carcinoma. These samples were from three locations: and were ≥10, 5 and ≤2 cm away from the proximal lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…On the other hand, ROCK1 overexpression is associated with colorectal cancer (CRC) [66,67]. Moreover, microRNA-148a and microRNA-21 inhibit DNA methyltransferase 1 (DNMT1) [68], an oncogene which is also overexpressed in CRC [69][70][71]. Indeed, incubation of CRC cells (Lim 1215) with human milk exosomes increased the cellular content of microRNA-148a [5], and addition of milk exosomes to normal intestinal cells (CRL 1831) significantly decreased DNMT1 expression [5,24].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, ROCK1 overexpression is associated with colorectal cancer (CRC) [66,67]. Moreover, microRNA-148a and microRNA-21 inhibit DNA methyltransferase 1 (DNMT1) [68], an oncogene which is also overexpressed in CRC [69][70][71]. Indeed, incubation of CRC cells (Lim 1215) with human milk exosomes increased the cellular content of microRNA-148a [5], and addition of milk exosomes to normal intestinal cells (CRL 1831) significantly decreased DNMT1 expression [5,24].…”
Section: Discussionmentioning
confidence: 99%
“…The protein content and size of bovine milk exosomes was significantly reduced in fermented cow's milk associated with a substantial loss of miRs (miR-29b, miR-21) compared to unfermented raw milk [48]. Malignant epithelial cells of CRC exhibit a reduced Melnik and Schmitz J Transl Med (2019) 17:3 expression of miR-148a [267][268][269][270], which increases the expression of DNMT1 that functions as a tumor promoter in CRC [271][272][273]. Intriguingly, Golan-Gerstl et al [44] demonstrated that the incubation of CRC cells (Lim 1215) with human breastmilk exosomes increased the cellular content of miR-148a.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Previously, we illustrated that the expression of DNMT1 was significantly higher in GC tissues than in non-GC tissues by meta-analysis[8]. Simultaneously, several studies have also revealed that DNMT1 was strongly expressed in GC and CRC[9,10], suggesting that DNMT1 could be a potential biomarker in screening of GI cancer.…”
Section: Introductionmentioning
confidence: 96%